UPAYA PENINGKATAN TEKNIK LAY UP BOLABASKET MELALUI METODE PEMBELAJARAN BERSERI PADA SISWA KELAS X.5 DI SMA NEGERI 16 MAKASSAR - Yusuf, Yusuf (UNIVERSITAS NEGERI MAKASSAR, 2018)
This study aims to determine the effect of serial learning training exercises in an effort to improve bolababasket lay-up techniques. By using the field experiment method. The population used is class X.5 students at Makassar State High School 16 with a sample of 32 students. To analyze complex data, researchers will use qualitative analysis techniques, one of which is interactive analysis techniques. The results of the study show that; the results of the recapitulation between cycles after going through the series of learning in the second cycle showed that the lay-up technique in basketball games in class X.5 students in Makassar 16 High School had an increase, it was shown from the results in cycle I there were 3 students (9.4% ) on a scale of 4 (good) and increased to 9 students (28.1%), resulting in an increase of 18.7% (28.1% - 9.4%). Likewise on the value scale 3 (medium category) shows that in the first cycle there were 12 students (37.5%) and increased to 23 students (71.9%) so that an increase of 34.4% (71.9% - 37, 5%). Thus it can be concluded that through serial learning carried out in the second cycle had an increase of 53.1% (18.7% + 34.4%) in the lay-up technique in basketball games for students of class X.5 in Makassar State High School 16.